Impact of a Prohibitive Versus Restrictive Tobacco Policy on Liver Transplant Candidate Outcomes. Issue 8 (4th July 2019) - Likhitsup, Alisa; Hassan, Ammar; Mellinger, Jessica; Askari, Frederick; Winder, Gerald S.; Saeed, Naba; Sonnenday, Christopher J.; Sharma, Pratima; Fontana, Robert J.
Abstract : Tobacco use has been associated with poorer outcomes after liver transplantation (LT). Our study examined the effect on LT listing outcomes of a newly implemented policy prohibiting the use of all tobacco products compared with a prior restrictive policy. Medical records of consecutive adult patients evaluated for LT from January 2010 to July 2013 (era 1, n = 1344) and August 2013 to March 2017 (era 2, n = 1350) were reviewed. The proportion of LT candidates listed was the primary outcome. The mean age of the 2694 LT candidates was 54 ± 11 years, 60% were male, and the mean Model for End‐Stage Liver Disease (MELD) score was 15 ± 7. Although the proportion of LT candidates who were smokers was significantly higher in era 2 (33% versus 23%; P  < 0.005), the proportion of smokers listed for LT remained stable (13% versus 17%; P  = 0.25). However, there were more smokers excluded for ongoing tobacco use in era 2 compared with era 1 (9.6% versus 4.4%; P  = 0.001). Factors independently associated with LT listing included a diagnosis of hepatocellular carcinoma, being married, private insurance, absence of psychiatry comorbidity, and absence of tobacco, marijuana, or opiate use but evaluation during era 2 was not associated with LT listing. However, the median time to listing significantly increased over time, especially in smokers (from 65 to 122 days; P  = 0.001), and this trend was independently associated with evaluation during era 2, a lower MELD score, not having children, and a lower level of education ( P  < 0.05). In conclusion, despite an increasing incidence of active smokers being referred for LT evaluation, the proportion of smoker candidates listed for LT was unchanged after instituting our prohibitive tobacco use policy. However, the time to get on the waiting list for smokers who were eventually listed was significantly longer due to the need to achieve complete tobacco cessation.